2022
DOI: 10.18433/jpps32892
|View full text |Cite
|
Sign up to set email alerts
|

Critical Remarks on Reference-Scaled Average Bioequivalence

Abstract: Purpose: More than a decade ago the option to assess highly variable drugs / drug products by reference-scaled average bioequivalence was introduced in regulatory practice. Recommended approaches differ between jurisdictions and may lead to different conclusions even for the same data set. According to our knowledge, implemented methods have not been directly compared for their operating characteristics (Type I Error and power). Methods: We performed Monte Carlo simulations to assess the consumer risk and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Figure 4 presents the data, collected via a simple paired design, in which each pig delivered two skin samples respectively treated with one of the two drugs of interest. Such designs, possibly attractive for studies not involving regulators, are stricto sensu incompatible with the use of design‐specific SABE‐like corrections 26 and therefore interesting to showcase the advantages of our design‐agnostic method. In order to assess bioequivalence of both topical treatments, the TOST and α$$ \alpha $$‐TOST procedures, based on a paired t$$ t $$‐test statistic considering ECZ levels on the logarithmic scale, are conducted using c=δU=prefix−δL=logfalse(1.25false)prefix≈0.223$$ c={\delta}_U=-{\delta}_L=\log (1.25)\approx 0.223 $$.…”
Section: Evaluation Of Bioequivalence For Econazole Nitrate Depositio...mentioning
confidence: 99%
“…Figure 4 presents the data, collected via a simple paired design, in which each pig delivered two skin samples respectively treated with one of the two drugs of interest. Such designs, possibly attractive for studies not involving regulators, are stricto sensu incompatible with the use of design‐specific SABE‐like corrections 26 and therefore interesting to showcase the advantages of our design‐agnostic method. In order to assess bioequivalence of both topical treatments, the TOST and α$$ \alpha $$‐TOST procedures, based on a paired t$$ t $$‐test statistic considering ECZ levels on the logarithmic scale, are conducted using c=δU=prefix−δL=logfalse(1.25false)prefix≈0.223$$ c={\delta}_U=-{\delta}_L=\log (1.25)\approx 0.223 $$.…”
Section: Evaluation Of Bioequivalence For Econazole Nitrate Depositio...mentioning
confidence: 99%
“…Figure 4 presents the data, collected via a simple paired design, in which each pig delivered two skin samples respectively treated with one of the two drugs of interest. Such designs, possibly attractive for studies not involving regulators, are stricto sensu incompatible with the use of design-specific SABE-like corrections 26 and therefore interesting to showcase the advantages of our design-agnostic method. In order to assess bioequivalence of both topical treatments, the TOST and α -TOST procedures, based on a paired t -test statistic considering ECZ levels on the logarithmic scale, are conducted using c = δ U = − δ L = log(1.25) ≈ 0.223.…”
Section: Evaluation Of Bioequivalence For Econazole Nitrate Depositio...mentioning
confidence: 99%
“…These recommendations were issued by the European Medicines Agency (EMA) and the US Food and Drug Administration (FDA) (see e.g., Muñoz et al, 2016; Davit et al, 2012, for more details). The amount of expansion is limited by the authorities, and several recent publications have shown that the TIER can be larger than the nominal level α (see e.g., Wonnemann et al, 2015; Muñoz et al, 2016; Endrenyi and Tothfalusi, 2019; Molins et al, 2021; Schütz et al, 2022, and the references therein) and therefore have proposed different ways to correct for it (see also Labes and Schütz, 2016; Tothfalusi and Endrenyi, 2016; Ocaña and Muñoz, 2019; Deng and Zhou, 2020). These corrections not only ensure that the TIER is smaller than or equal to α , but also lead to acceptance regions that change more smoothly with σ ν .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations